PENGARUH CITRA MEREK, INOVASI PRODUK, DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK DEODORANT CASABLANCA MASYARAKAT NAN SABARIS KABUPATEN PADANG PARIAMAN - Mulyani, Sri; Septiani, Dina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
This research aims to find out how big the influence of brand image, product innovation and advertisement to purchase decision on Casablanca deodorant product at Nan Sabaris Subdistrict, Padang Pariaman regency partially and influence of brand image, product innovation and advertisement to purchase decision on Casablanca deodorant product on society District Nan Sabaris Padang Pariaman simultaneously. This type of research is associative research and is used for explanatory purposes. This research method is quantitative method. The population in this study is the community in District Nan Sabaris Padang Pariaman Limpato, where samples are 84 respondents. Data collection techniques were conducted with interviews and questionnaires. The data was processed using SPSS version 17. The result showed that brand image, product and advertising innovation had a positive effect partially to the purchase decision on deodorant casablanca product in Nan Sabaris sub-district, Padang Pariaman regency and brand image, product and advertising innovation had positive effect simultaneously to purchase decisions on deodorant casablanca products in the community of Nan Sabaris Sub-district, Padang Pariaman District. With multiple linear regression is Y = 0,916 + 0,425X1 + 0,410X2 + 0,189X3 and coefficient of determination give contribution equal to 51%. With the positive relationship between brand image (X1), product innovation (X2) and advertisement (X3) on purchasing decision (Y) deodorant casablanca product in Nan Sabaris sub-district, Padang Pariaman, it is expected to increase sales revenue to always pay attention to things. things that can attract the attention of consumers or customers so that it can lead to purchasing decisions.